A THE RELATIONSHIP OF ARM MUSCLE STRENGTH AND EYE COORDINATION TO SHOOTING ABILITY IN BASKETBALL GAMES IN STUDENTS SMAN 1 SEISUKA COAL REGENCY: basketball - Andi Nur Abady Abady; Fajar Sidik Siregar; ahamad Al Munawar; Muhammad Syaleh -; devi catur winata (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2022)
This study aims to determine: (1) There is a relationship between eye-hand coordination and shooting skills in the basketball game of students at SMAN 1 Seisuka, Batubara Regency. (2) Whether or not there is a relationship between arm muscle strength and shooting ability in basketball games for students at SMAN 1 Seisuka, Batubara Regency. (3) There is a relationship between hand eye coordination and arm muscle strength on shooting skills in basketball games for students at SMAN 1 Seisuka, Batubara Regency. The population is all students of SMAN 1 Seisuka, Batubara Regency, the sample used is 30 male students, the sampling technique is purposive sampling technique. The data analysis technique used is descriptive analysis, person product moment correlation coefficient analysis (r) and multiple correlation analysis (R) at a significant level of 0.5. The results showed that: (1) There was a significant relationship between eye-hand coordination and shooting skills in the basketball game of students at SMAN 1 Seisuka, Batubara Regency with an r value of 0.537. (2) There is a significant relationship between arm muscle strength and shooting ability in the basketball game of SMAN 1 Seisuka students, Batubara Regency with an r value of 0.611. (3) There is a significant relationship between hand eye coordination and arm muscle strength together with the shooting ability of the basketball game students of SMAN 1 Seisuka, Batubara Regency with an R value of 0.740, for the determinant coefficient value of 54.8%. Conclusion: There is a significant relationship between hand eye coordination and arm muscle strength on shooting ability.